Assessing the combined effect of gamma radiation and sulfate-reducing bacteria on copper corrosion for deep nuclear waste storage - Morales-Hidalgo, Mar; Povedano-Priego, Cristina; Martinez-Moreno, Marcos F.; Mumford, Adam D.; Černá, Kateřina; Ju-Nam, Yon; Ojeda, Jesus J.; Fernández, Ana María; Alonso, Ursula; Jroundi, Fadwa; Merroun, Mohamed L. (Corrosion science, 2026)
Ensuring the integrity of containment barriers in geological disposal facilities (GDFs) is crucial for the long-term storage of radioactive waste. Copper is considered as a promising canister material due to its corrosion resistance. This study examines the combined effects of external gamma radiation (14 and 28 kGy) and sulfate-reducing bacteria (SRB) on copper corrosion in highly compacted FEBEX bentonite. Results showed that gamma radiation significantly reduces SRB viability, suggesting that these bacteria are likely to remain inactive during the early centuries of GDF operation, when radiation is at its highest level. Microscopic and spectroscopic analyses identified copper oxides, particularly CuO, as the main corrosion products. Gamma radiation was found to delay microbially influenced corrosion by altering the microbial community structure and promoting salt precipitation, including copper sulfates. SRB facilitated the formation of biogenic copper sulfides on unirradiated samples or those minimally affected by radiation. These findings provide valuable insights into the role of SRB in copper corrosion, broadening the understanding of long-term GDF safety. [Display omitted] •Gamma radiation reduces SRB viability, delaying copper biocorrosion.•Copper oxides were the main corrosion products in all bentonite-treated blocks.•SRB-driven biogenic copper sulfides appeared in unirradiated treatments.•XPS revealed abiotic CuxS formation in Cu exposed to highest radiation dose (28 kGy).